2016
DOI: 10.1080/15476286.2016.1195940
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome fusions triggered by noncoding RNA

Abstract: Chromosomal fusions are common in normal and cancer cells and can produce aberrant gene products that promote transformation. The mechanisms driving these fusions are poorly understood, but recurrent fusions are widespread. This suggests an underlying mechanism, and some authors have proposed a possible role for RNA in this process. The unicellular eukaryote Oxytricha trifallax displays an exorbitant capacity for natural genome editing, when it rewrites its germline genome to form a somatic epigenome. This dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The above observations related to MIC-limited non-repetitive eccDNA are consistent with a general model in which widespread DNA cleavage occurs preferentially outside of regions protected by Oxytricha piRNAs that mostly mark MDSs, with sparser mapping to non-coding subtelomeric regions and almost no mapping to IESs (13,66). Such a coarse method of eliminating DNA may be helpful in reducing the sequence space that needs to be searched before more complex rearrangements occur, but it also implicates a need for maternal RNA template-guided error correction and repair (11,12,67).…”
Section: Discussionsupporting
confidence: 86%
“…The above observations related to MIC-limited non-repetitive eccDNA are consistent with a general model in which widespread DNA cleavage occurs preferentially outside of regions protected by Oxytricha piRNAs that mostly mark MDSs, with sparser mapping to non-coding subtelomeric regions and almost no mapping to IESs (13,66). Such a coarse method of eliminating DNA may be helpful in reducing the sequence space that needs to be searched before more complex rearrangements occur, but it also implicates a need for maternal RNA template-guided error correction and repair (11,12,67).…”
Section: Discussionsupporting
confidence: 86%
“…Previous research demonstrated that injection of synthetic DNA or RNA copies of chromosomes during nuclear development can specifically influence DNA rearrangement in the subsequent generation (Nowacki et al 2008; Nowacki et al 2010; Bracht et al 2017). To further investigate the influence of exposure to a synthetic DNA molecule during conjugation, we injected a copy of wild type Contig16116.0, the nanochromosome encoding the Otiwi1 gene, into O. trifallax cells.…”
Section: Resultsmentioning
confidence: 99%
“…Given our knowledge that macronuclear chromosome architecture relies on the transfer of parental epigenetic information across sexual generations (Nowacki et al 2008; Fang et al 2012; Bracht et al 2017), we examined the influence across generations of loss or copy number reduction of targeted nanochromosomes. Because the deletion lines for Contigs 17155.0 and 9679.0 target genes are under further investigation elsewhere (Yerlici et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that some isoforms derive exclusively from one locus or the other also raises the question of what regulates this selection and what determines the range of isoforms produced. The finding that piRNAs can strongly influence chromosome fragmentation patterns and lead to alternatively processed chromosomes [26] suggests that the piRNA pathway is involved [27, 28] in this process.…”
Section: Discussionmentioning
confidence: 99%